Effect of Two Different FSH Doses on Superovulatory Response and Embryo Production in Sahiwal Cows - Imtiyaz, N.; Brar, P. S.; Singh, N.; Malik, V. S. (The Indian Journal of Animal Reproduction, 2021)
The study was conducted to evaluate the effect of two different doses of FSH on superovulatory responses in Sahiwal cows. Twelve normally cyclic pluriparous Sahiwal cows weighing between 350 and 450 kg were superstimulated using two different doses of Folltropin-V (100 mg vs 200 mg of NIH FSH PI). Prior to superstimulation, the cows were administered estradiol-17β (2 mg, IM) with placement of intravaginal progesterone releasing device (TRIU-B) at the random stage of the estrous cycle (Day 0). From day 4 onward, cows were administered Folltropin-V @100 mg in the group 1 and 200 mg of NIH FSH PI in the group 2; the total dose was divided into 8 tapering doses given at 12 hourly intervals in both the groups. Prostaglandin F2α analogue (PGF2α) was administered at day 6 and 6.5; TRIU-B was removed with the last FSH injection. All cows in both the groups were inseminated twice at 12 and 24h of LH treatment. Daily ultrasonography was performed to record the size and number of follicles and superovulatory response. Results showed that the number of small follicles (≤7 mm) present at the time of initiation of superstimulatory treatment did not differ between both the groups (23.3±3.93 vs. 22.3±1.17, p>0.05). Following superstimulatory treatment, the average number of small follicles reaching ovulatory size (>10 mm) were 18.0±4.04 and 19.2±1.11 in the group-1 and the group-2, respectively; the difference was non significant (p>0.05). Similarly, the total embryos and transferable embryos recovered also did not differ between the group-1 and the group-2 (9.0±4.02 vs 10.7±2.78; p>0.05, and 3.5±1.26 vs 3.3±1.84; p>0.05, respectively). The study showed that low dose of follicle stimulating hormone i.e. 100 mg is equally effective as 200 mg of NIH FSH PI in inducing superstimulation and embryo production in Sahiwal cows.